A new approach for sustained and efficient H2 photoproduction by Chlamydomonas reinhardtii. Issue 6 (17th April 2018) - Kosourov, Sergey; Jokel, Martina; Aro, Eva-Mari; Allahverdiyeva, Yagut
Abstract : Pulse-illumination re-directs photosynthetic electron flow destined for CO2 fixation to [FeFe]-hydrogenase, thus sustaining algal H2 photoproduction for 70 hours. Abstract : Sustained H2 photoproduction is demonstrated in green algae under a train of strong white light pulses interrupted by longer dark phases. The devised protocol relies on the presence of the [FeFe]-hydrogenase in algal chloroplasts, which is activated within a few seconds after the establishment of anaerobiosis. H2 photoproduction proceeds for up to 3 days with the maximum rate occurring in the first 6 hours.